2016
DOI: 10.1007/s00430-016-0459-9
|View full text |Cite
|
Sign up to set email alerts
|

NK cells contribute to persistent airway inflammation and AHR during the later stage of RSV infection in mice

Abstract: RSV can lead to persistent airway inflammation and AHR and is intimately associated with childhood recurrent wheezing and asthma, but the underlying mechanisms remain unclear. There are high numbers of NK cells in the lung, which not only play important roles in the acute stage of RSV infection, but also are pivotal in regulating the pathogenesis of asthma. Therefore, in this study, we assumed that NK cells might contribute to persistent airway disease during the later stage of RSV infection. Mice were killed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…However, other studies have shown that, unlike AhR protein expression, which is decreased in inflamed CD tissues, there is no difference in AhR gene expression between tissues from CD patients and healthy controls. 149 The involvement of post-transcriptional mechanisms may explain the disparity between AhR gene and protein expression. This is consistent with a study showing that miRNA-124, which is involved in post-ranscriptional gene regulation and had been shown to have a pro-inflammatory role in TNBS-induced colitis by suppressing AhR, is highly expressed in inflamed biopsies and IECs from CD patients.…”
Section: Ahr In Gut Inflammationmentioning
confidence: 99%
“…However, other studies have shown that, unlike AhR protein expression, which is decreased in inflamed CD tissues, there is no difference in AhR gene expression between tissues from CD patients and healthy controls. 149 The involvement of post-transcriptional mechanisms may explain the disparity between AhR gene and protein expression. This is consistent with a study showing that miRNA-124, which is involved in post-ranscriptional gene regulation and had been shown to have a pro-inflammatory role in TNBS-induced colitis by suppressing AhR, is highly expressed in inflamed biopsies and IECs from CD patients.…”
Section: Ahr In Gut Inflammationmentioning
confidence: 99%
“…Viral‐induced type 2 inflammation has also been observed in other pulmonary viral infections such as those caused by RSV or rhinovirus (RV) . Severe primary infections with RSV or RV during infancy are generally associated with a development of allergy and asthma later in life, as well as with severe and life‐threatening exacerbations in adult patients suffering from chronic obstructive disease (COPD), pneumonia or asthma .…”
Section: Role Of Ilcs In Lung Infection and Ilc Immunitymentioning
confidence: 99%
“…The single cell suspensions of mouse lung tissue were prepared as described previously [9]. Samples were blocked with rat serum for 20 min, and then immunostained with antibody to mouse CD45, CD3, CD49b, CD19, F4/80, CD11c, CD11b, Ly6G, Ly6C or isotype control conjugated with PerCP-cy7, PerCP-cy5.5, PE, FITC or APC for 30 min on ice.…”
Section: Flow Cytometry Analysismentioning
confidence: 99%
“…Both epidemiological studies and animal experiments have demonstrated that exposure to LPS can sensitize or exacerbate COPD and asthma by promoting Th2 responses [8]. We have identified that a Th2 cytokines-dominant airway microenvironment similar to asthma was triggered during the later stage of RSV infection [9]. However, it's not clear whether inhalation of LPS might boost RSV-associated airway inflammation and AHR by increasing Th2 responses.…”
Section: Introductionmentioning
confidence: 99%